Konkurencyjność polskiego systemu podatkowego na tle państw należących do OECD - Sokołowski, Jerzy (Competitiveness of the Polish Tax System Against OECD Countries, 2005)
The author analyses the level of competitiveness of the Polish tax system against OECD countries. The first aspect undergoing a comparative analysis is the rates of personal income tax, corporate income tax, and VAT. The article also points out that competitiveness of a tax system depends not only on the rates applied, but also on long-term predictability of tax law. An other implication discussed is the possibility of influencing investors' decisions through local taxes.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 352-356